Densification, rent and use value - Ploštajner, Klemen (Teorija in praksa, 2021)
Since 2015, the residential neighbourhood of Rožna dolina has experienced intense building activity that has been supported by the city of Ljubljana, but has been met with resistance from the local inhabitants, thus becoming the most visible local expression of the universal capitalist conflict between the use and exchange value of space. The article main aim is to analyse the concrete manifestation of this conflict by looking at the operations of the local state, investors and inhabitants in the production of space in Rožna dolina. The analysis shows that the conflict is influenced by the specific local state's dependency on economic actors, by specifics of local real estate market and workings of developers and by the composition of inhabitants of Rožna dolina.
Keywords: apropriacija; Local government; Lokalna samouprava; Nasprotja interesov; nepremičninske investicije; Poslovanje z nepremičninami; prostorski konflikti; Real estate business; renta